Legal Protection and Certainty for Children Born Out of Wedding Through Legal Remedies Recovering the Child's Origin in the Court (Analysis of Decision Number 196/Pdt.P/2023/Pn.Cbi) - Salimah, Alvy Nur; Satory, Agus; Mahipal, Mahipal (Civiliza Publishing, 2025)
Legal protection and guarantees for illegitimate children are crucial issues in the Indonesian family law system, as their legal status often faces discrimination and uncertainty regarding the recognition of civil relationships, inheritance, and access to basic rights. This study aims to examine legal steps that can be taken to provide legal protection and guarantees for illegitimate children, particularly through the process of applying for a determination of the child's parentage in court. Using a normative juridical approach and case analysis, this study analyzes relevant legal provisions, court decisions, and the principles of human rights and the best interests of the child as stipulated in the Convention on the Rights of the Child and national regulations. The research findings reveal that although illegitimate children have historically faced a number of legal obstacles, developments in jurisprudence following Constitutional Court Decision No. 46/PUU-VIII/2010 have provided an opportunity for the recognition of civil relationships between children and their biological fathers through the process of applying for a determination of parentage in court. However, implementation in the field continues to face obstacles, both procedural and socio-cultural. Therefore, harmonization of legal norms, increased capacity of judicial officials, and extensive outreach are needed to ensure that every child, regardless of their origin, receives fair and non-discriminatory legal protection and certainty.